Hannibal - Scott, Ridley; Hopkins, Anthony, 1937-; Moore, Julianne; Giannini, Giancarlo; MGM Home Entertainment Inc. (Santa Monica, CA : Distributed by Metro Goldwyn Mayer Home Entertainment, 2004)
One of Dr. Hannibal Lecter's surviving victims is poised to enact sweet revenge on the world's most feared cannibal. FBI agent Clarice Starling is brought back on the case when Lecter decides to come out of retirement to face his adversary.
Title from container.
Originally released as a motion picture in 2001.
Special features: original theatrical trailer.
Director of photography, John Mathieson ; editor, Pietro Scalia ; music, Hans Zimmer.
Anthony Hopkins, Julianne Moore, Giancarlo Giannini, Ray Liotta, Frankie R. Faison.
MPAA rating: R; strong gruesome violence, some nudity and language.
Keywords: Lecter, Hannibal (Fictitious character) -- Drama; Psychopaths -- Drama; Feature films; Video recordings for the hearing impaired